Application of composite materials to the chenda, an Indian percussion instrument. (February 2015) - Damodaran, Ajith; Mansour, Hossein; Lessard, Larry; Scavone, Gary; Suresh Babu, A.
Highlights: Acoustic drum shells were developed using composite materials. Damping measurements were carried out for wood and composites. Radiativity was compared for wooden and composite instrument. Composite manufacturing brings standardisation in drum shells. Abstract: An acoustically and structurally effective drum shell is developed for a traditional Indian drum. The basic design concept is a sandwich structure composed of carbon fibre/epoxy face sheet and balsa core on which the drum head is attached. The drum shell structure was fabricated by wet lay-up and a vacuum molding technique. Sound characteristics were analysed for both composite and wooden drums. Measured acoustical performance shows that the frequency response of the composite drum is comparable with that of a traditional wooden drum. It seems promising that composite materials with high damping characteristics could replace wooden structures used in musical instruments. Further, composite manufacturing helps in bringing standardisation and uniformity to musical instrument structures.